Pengaruh Pola Pikir Ibu Terhadap Kecenderungan Stunting di Desa Sidodadi - Al Farisi, Salman; Ainun Nisa, Afrakh; Zaenal Arifin, Mukhamad; Juliana, Putri; Nur Fitria, Rofidah; Makki Hasan, Ahmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Stunting is a slowing of growth in children whose height is shorter than children of their age and also has an impact on the psychological, intellectual, mental, psychological, and motor. As many as 43.5% of cases of stunting in Indonesia are experienced by children under five with a vulnerable mother's age between 14-15 and ages between 16-17 years as much as 22.4% are the result of early marriages. The purpose of this study was to find out how the mother's mindset influences the tendency of stunting in Sidodadi Village. This study uses a quantitative approach to the type of research to measure the value of the variables studied. Primary data is in the form of mother's mindset and upbringing, secondary data on stunting events which are influenced by mother's upbringing. The research sample consisted of 62 toddlers from 7 hamlets with an age range of 0-59 months as of August 2022. Data collection used a simple random sampling technique. Data on maternal parenting patterns were obtained through interviews with village midwives. From the data using the SPSS program, the maximum score on the mother's mindset scale is 24, the minimum score is 12 and the average is 18.22, while the maximum score on the parenting scale is 21, the minimum is 13 and the average is 15.59. From the associative test obtained an F value of 84.961 and a significance value of 0.000. Stunting in Sidodadi village is caused by several factors, one of which is parenting style and mother's mindset.